Korupsi di Indonesia dalam Perspektif Hierarki Kebutuhan Abraham Maslow - Felix Riondi Sugar; Bernardino Suryatno Agas; Petrus Paulus Molan Jawang; Eugenius Advento Luahane; Kristoforus Mage; Hironimus Naras; Apriliano Peterpen Ajen; Simplisius Seke Kawa (Lembaga Pengembangan Kinerja Dosen, 2026)
Corruption is one of the most significant challenges still facing Indonesia due to its far-reaching impact on social, economic, political, and legal life. Until now, corruption has largely been understood as a violation of the law or a failure of the government system. This article aims to analyze the phenomenon of corruption in Indonesia through the lens of Abraham Maslow’s Hierarchy of Needs to understand the psychological motivations underlying corrupt behavior. This study employs a qualitative method using a literature review approach, examining various scientific literature, books, journals, and data related to corruption in Indonesia. The findings indicate that corruption does not arise solely from economic needs but is also linked to distortions in the fulfillment of the need for security, social needs, the need for recognition, and the need for self-actualization. Corruption serves as a means to obtain power, social status, and instant recognition through the abuse of authority. Additionally, weak moral integrity and a materialistic culture further reinforce corrupt behavior. Therefore, combating corruption requires an approach that is not only focused on law enforcement but also on character building, moral education, and the cultivation of a culture of integrity in societal and national life.